Brand Image Determination, Price Perception, and Brand Trust in the Purchase Decision of Low Cost Carrier Airlines in Indonesia - Mustika Sari; Pantri Heriyati; Muhammad Thamrin; Fitri Maisarah Zahra (Universitas Pasundan, 2024)
The main objective of this study is to examine various factors that affect the consumer decision-making process when purchasing tickets from low-cost airlines in Indonesia. This study focuses on analyzing the influence of three main factors, namely brand image, price perception, and trust, on the final purchase choice. This study uses a quantitative methodology, using primary and secondary data sources. Primary data was obtained by providing questionnaires to low-cost carrier users to get a direct perspective from customers. This study shows that trust, price perception, and brand image are important variables influencing consumers’ decisions to buy low-cost carriers in Indonesia. The study’s findings show that LCC customers’ purchasing decisions are significantly influenced by their perceptions of brand image, trust, and pricing. Customers are more inclined to select airlines they believe to be dependable and safe, therefore trust is an important consideration. Another important factor is price perception, which shows how customers react to competitive pricing that matches the value they anticipate. Airlines that successfully create a green brand image and keep prices competitive can stand out in the market as consumers’ awareness of environmental issues grows. Empirical evidence from this study suggests that incorporating sustainability into business strategies may appeal to the increasing number of environmentally conscious consumers. Finally, airlines who are effective in creating a positive brand image stand out in the competitive low-cost carrier (LCC) sector, demonstrating the importance of brand image as a decision driver.